Aerosol‐Forced AMOC Changes in CMIP6 Historical Simulations. Issue 14 (22nd July 2020) - Menary, Matthew B.; Robson, Jon; Allan, Richard P.; Booth, Ben B. B.; Cassou, Christophe; Gastineau, Guillaume; Gregory, Jonathan; Hodson, Dan; Jones, Colin; Mignot, Juliette; Ringer, Mark; Sutton, Rowan; et al.
Abstract: The Atlantic Meridional Overturning Circulation (AMOC) has been, and will continue to be, a key factor in the modulation of climate change both locally and globally. However, there remains considerable uncertainty in recent AMOC evolution. Here, we show that the multimodel mean AMOC strengthened by approximately 10% from 1850–1985 in new simulations from the 6th Coupled Model Intercomparison Project (CMIP6), a larger change than was seen in CMIP5. Across the models, the strength of the AMOC trend up to 1985 is related to a proxy for the strength of the aerosol forcing. Therefore, the multimodel difference is a result of stronger anthropogenic aerosol forcing on average in CMIP6 than CMIP5, which is primarily due to more models including aerosol‐cloud interactions. However, observational constraints—including a historical sea surface temperature fingerprint and shortwave radiative forcing in recent decades—suggest that anthropogenic forcing and/or the AMOC response may be overestimated. Key Points: The Atlantic Meridional Overturning Circulation (AMOC) is important in modulating climate change, but its past evolution is uncertain In CMIP6 historical runs, the AMOC strengthens by ~10% as a response to increased forcing from aerosol indirect effects, unlike in CMIP5 Observational constraints suggest that anthropogenic forcing and/or the AMOC response may be overestimated